Cowpea genetic diversity, population structure and genome-wide association studies in Malawi: insights for breeding programs - Chipeta, Michael M.; Kafwambira, John; Yohane, Esnart (Frontiers in Plant Science, 2025)
IntroductionThis study focuses on cowpea, a vital crop for smallholder farmers in sub-Saharan Africa, particularly in Malawi. The research aimed to understand the genetic diversity and population structure of cowpea and to perform genome-wide association studies (GWAS) to identify marker-trait associations (MTAs) for yield and related traits. These insights are intended to support varietal development and address agricultural challenges in Malawi.MethodsA total of 306 cowpea genotypes were characterized using single nucleotide polymorphism (SNP) markers and morphological traits. The study assessed the effects of genotype, location, and their interactions on morphological traits. The Fixed and Random Model Circulating Probability Unification (FarmCPU) algorithm was used to identify significant MTAs.ResultsThe morphological traits showed significant genotype, location, and interaction effects. Genotypes MWcp24, MWcp47, MWcp2232, and TVu-3524 yielded the highest values. Grain yield was positively correlated with peduncle length, seeds per pod, and pods per plant. Three distinct clusters were identified based on morphological traits. Genetic diversity analysis revealed an average minor allele frequency of 0.31, observed heterozygosity of 0.06, and gene diversity of 0.33. The average inbreeding coefficient was 0.82, indicating a high level of inbreeding. Most of the genetic variation (73.1%) was found among genotypes within populations. Nine groups and ancestral populations were identified, which did not entirely overlap with geographic origins. Sixteen significant MTAs were linked to six morphological traits.DiscussionThe validation of these identified MTAs, along with the observed genetic diversity, offers valuable opportunities for cowpea improvement through marker-assisted selection, to addresses the challenges faced by Malawian farmers. The identification of thirty cowpea lines as key founder lines for breeding programs in Malawi, Mozambique, and Tanzania is a significant outcome. These efforts aim to develop more productive cowpea lines for the region, enhancing food security and agricultural sustainability.